USM RESEARCHER SUSTAINS EXCELLENCE WITH THREE PUBLICATIONS IN HIGH-IMPACT JOURNAL - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, KELANTAN, 25 April 2016 “ Publications in highimpact journals would normally require teamwork in exercising data collection and analysis, and in the publication of those articles.”